Intellectual capital's role in shaping corporate financial performance from a knowledge-based theory perspective - Tasrim Tasrim; Ansri Jayanti; Estiani Estiani; Tyagita Dianingtyas Sudibyo Sudibyo (Institute of Computer Science (IOCS), 2023)
Performance is a condition that is always a concern for managers. Conditions that are easy to